Spirituality in entrepreneurship from Islamic perspectives: a conceptual analysis on the effects on entrepreneurial motivation and social responsibility - Mohammed Adamu, Isa; Kedah, Zulkarnain; Osman-Gani, Aahad M. (2011)
Spirituality in entrepreneurship as an emerging area of interest has begun to generate attention from management scholars. However, most research in this area is from the western perspective. Until recently, there is dearth of research that gears towards spirituality in Islam and its contribution to the overall development of modern organisations. This exploratory study presents a conceptual analysis of the effects of spirituality in Islam on entrepreneurial motivation, performance and commitment to social responsibility. It has been suggested that spirituality in Islam has the potential to positively influence the entrepreneurial outcomes considered.